The VR-AI–Assisted Simulation for Content Knowledge Application in Pre-Service EFL Teacher Training - Pitura, Joanna; Kaplan-Rakowski, Regina; Asotska-Wierzba, Yuliya (TechTrends, 2025)
Pre-service teachers (PSTs) of English as a Foreign Language (EFL) need extensive training, preparing them for challenges encountered in real classrooms. Such challenges include presenting the target content knowledge in front of the class and promptly responding to students’ questions on the content. High-immersion virtual reality (VR) is increasingly seen as technology facilitating teacher training. When integrated with Artificial Intelligence (AI), VR simulations can enhance teacher education by providing real-world practice opportunities. Drawing on cognitive flexibility theory (CFT), this case study investigated how pre-service EFL teachers ( N = 17) in Poland interpret the VR-AI–assisted simulation designed to facilitate their content knowledge application. The results suggest that such simulations are valuable for professional development and reflective practice regarding content knowledge in pre-service EFL teacher training. The findings contribute to the broader understanding of the integration of VR and AI technology in language teachers’ training programs aiming to support the application of content knowledge in real-life classrooms.